COMPARATIVE ANALYSIS OF MERGERS AND ACQUISITIONS WITHIN THE NEW MEMBER STATES OF THE EU UNION - FANDY, DR. YON (International Journal of Multidisciplinary Research and Studies, 2020)
Mergers and acquisitions within the new member states of the EU Union (EU-10) are investigated within the study. The author concentrates on the mergers and acquisitions value creation issue within the region. The event study methodology is used to research the scientific problem useful generation as a consequence of analyzed transactions. Findings of the study show that there’s a statistically significant positive effect observed when analyzing value variations as a results of mergers and acquisitions happening within the EU-10 region. However, there are great differences observed when different countries or groups of states are analyzed in EU-10. This finding supports the conclusions of previous researches within the field stating that value creation in mergers and acquisitions varies greatly in separate regions or countries. it had been also found during the research that transactions going down within the Baltic states have generated the very best value increase in EU-10 during the amount of 2004–2013.